Penggunaan Media Grafis Untuk Meningkatkan Minat Belajar Matematika pada Materi Pengolahan Data - Nandang Kusnandar (STKIP Sebelas April Sumedang, 2020)
This research is motivated by the low interest of students in learning mathematics in data processing material. One of the media that can be used for learning mathematics data processing material is by using graphic media. This study has a purpose, namely to describe the increase in student interest in learning by using graphic media. The author uses the Classroom Action Research (CAR) method. The subjects of this research were the students of class VI SDN Darangdan Level, amounting to 21 people. The research data were collected through a questionnaire and a written test. After the use of graphic media, it can be seen that there is an increase in student interest and learning outcomes. This can be seen from the student learning interest questionnaire data in the first cycle, the percentage of student interest in learning who got the very good category was 0%, the good category was 57%, enough category was 33%, and the less category was 10%. Then in the second cycle, it increased to 19% very good category, 71% good category, 10% sufficient category, and 0% less category. Then the increase in student learning outcomes can be seen with an increase that occurs from the initial data obtained an average student learning outcome of 55.14 with the number of students who completed as many as seven people (33%), the first cycle obtained an average score of 68 student learning outcomes, 09 with the number of students who completed as many as 11 people (52%), and in the second cycle, the average value of student learning outcomes was 79.04 with the number of students who completed as many as 19 people (90%).